Treatment of non-small cell lung cancer using chem-bioinformatics-driven engineering of exosomal cargo-vehicle for telmisartan and pioglitazone targeted-delivery - Nadia M. Hamdy; Eman F. Sanad; Shaymaa E. Kassab; Merhan Essam; Monica A. Guirguis; Emad B. Basalious; Ahmed S. Sultan (Scientific Reports)
Abstract The activation of the PPARG transcription factor is linked to reduced non-small cell lung cancer (NSCLC) growth. Bioinformatics, cheminformatics, and molecular docking/dynamics studies assessing pioglitazone and telmisartan as repurposed PPARG agonists for treating NSCLC with a targeted delivery system was done. Bioinformatics confirmed that the expression of the PPARG gene can predict outcomes in lung adenocarcinoma and is related to immune cells present in the tumor. Cheminformatics data showed that pioglitazone and telmisartan have a strong attraction to the PPARG receptor, with good efficiency as ligands. Both drugs were found to be lipophilic, suggesting compatibility with a targeted delivery formulation that may include albumin. Further cheminformatics predictions highlighted systemic toxicity values and the need for targeted delivery to minimize toxic side effects. Molecular docking and dynamics simulations showed that the telmisartan-MyoVc cargo domain complex was strong and stable during an 18 ns simulation period. Bioinformatics and cheminformatics data support pioglitazone and telmisartan as promising repurposed drugs for LUAC, highlighting their lipophilicity and compatibility with exosomal components like albumin. Cheminformatics also pointed out potential off-target effects and hepatotoxicity, emphasizing the importance of exosomal targeted delivery. Molecular docking and MD simulations confirmed the affinity and stability of drug-exosomal vehicle complexes. The proposed engineering of exosomal cargo for targeted delivery of these drugs to lung cells could enhance NSCLC treatment and address drug resistance while minimizing systemic toxicity.